Is heart transplantation a real option in patients with Duchenne syndrome? Inferences from a case report. (1st August 2020) - Piperata, Antonio; Bottio, Tomaso; Toscano, Giuseppe; Avesani, Martina; Vianello, Andrea; Gerosa, Gino
Abstract: Duchenne muscular dystrophy (DMD) is the most frequent and severe form of MD. It firstly affects the skeletal muscles, causing severe disability, and subsequently the myocardium. The only two options to treat end‐stage heart failure in these patients are either a left ventricular assist device (LVAD) implantation as destination therapy or a heart transplant. These hypotheses are still controversial, and data are very limited. We describe the case of an 18‐year‐old male patient, affected by DMD and in a wheelchair from the age of 11. He progressively developed dilated cardiomyopathy, and in 2016, at the age of 14 years, he underwent HeartWare LVAD implantation, as destination therapy, without post‐operative complications. He has been followed up for 47 consecutive months; and 30 months after LVAD implantation, he developed an infection of the exit site, treated by antibiotics and surgical toilette. Following this event, on the basis of patient's good general conditions and willingness, we started to consider heart transplant as an option. Before the patient was listed, he underwent accurate workup, and we found higher values of forced vital capacity, forced expiratory volume in 1 s, and peak expiratory flow, compared with the predicted values of same‐age DMD patients. The patient have neither scoliosis nor need for non‐invasive mechanical ventilation, and finally, he was always treated with steroids with stable thoraco‐abdominal function over the years. According to these considerations, the patient was listed for heart transplant. In 12 February 2020, at the age of 18 years, the patient underwent heart transplant with no post‐operative complications. Cardiac transplantation is not considered a valid option for DMD patients, because of the shortage of donor availability and the systemic nature of DMD disease. Considering that this patient had already experienced an LVAD‐related complication and he had better general condition than his DMD peers, we listed him for a heart transplant. We described the case of a DMD patient who underwent successful heart transplantation after 47 months of HeartWare LVAD assistance. Three months' follow‐up is uneventful.